1991
DOI: 10.1007/bf00634975
|View full text |Cite
|
Sign up to set email alerts
|

The peak oxygen uptake of British children with reference to age, sex and sexual maturity

Abstract: The purposes of this study were to provide baseline data on the peak oxygen consumption (VO2) of British children, aged 11-16 years and to examine the peak VO2 of children in relation to their pubertal stage of development. The peak VO2 of 226 boys and 194 girls was determined during either treadmill running or cycle ergometry. The sexual maturity of 320 of the children was estimated using Tanner's indices. Peak VO2 increased with chronological age in both sexes and from about the age of 12 years boys exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
74
4
6

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 15 publications
15
74
4
6
Order By: Relevance
“…[56][57][58][59][60] Reports also point out that a cycle ergometer test may require an average of 10 additional minutes to achieve maximal effort than tests on treadmills, 61 because (i) subjects on the cycle ergometer have an inability to keep up with their performance; [61][62][63] (ii) a greater activation of MedicalExpress (Sao Paulo, online) 2016 February;3(1):M160102 Cardiopulmonary exercise testing in healthy children Tavares AC large amounts of muscle mass occurs during a treadmill test; 58,59,61 (iii) more discomfort in the thigh muscles occurs during the cycle ergometer test; (iv) less intensity of effort and protocol duration to maximize aerobic energy transfer is achieved on the cycle ergometer. 57,59,61 The 18-20% differences on peak VO 2 values found in this analysis were similar to the 22% difference reported elsewhere; 61 however, smaller differences have also been reported: 7%, 61 8%, 24,64 or 12% higher on a treadmill.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…[56][57][58][59][60] Reports also point out that a cycle ergometer test may require an average of 10 additional minutes to achieve maximal effort than tests on treadmills, 61 because (i) subjects on the cycle ergometer have an inability to keep up with their performance; [61][62][63] (ii) a greater activation of MedicalExpress (Sao Paulo, online) 2016 February;3(1):M160102 Cardiopulmonary exercise testing in healthy children Tavares AC large amounts of muscle mass occurs during a treadmill test; 58,59,61 (iii) more discomfort in the thigh muscles occurs during the cycle ergometer test; (iv) less intensity of effort and protocol duration to maximize aerobic energy transfer is achieved on the cycle ergometer. 57,59,61 The 18-20% differences on peak VO 2 values found in this analysis were similar to the 22% difference reported elsewhere; 61 however, smaller differences have also been reported: 7%, 61 8%, 24,64 or 12% higher on a treadmill.…”
Section: Discussionsupporting
confidence: 88%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Among all included trials, 12 studies (60%) used the Tanner-Whitehouse evaluation scale to analyze children's maturation. 20 One study chose the Weber method, 21 whereas one identified the sample as pre-menarchal and therefore this analysis considered the population as prepubertal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Con- Quando realizamos um ajuste exponencial para normalização do VO 2max em relação à massa corporal (ml.kg 0,67 .min -1 ), que, segundo alguns autores 21,22 , remove as diferenças de dimensão corporal que podem inter-cordando com estudos anteriores 25,26 , verificou-se que o VO 2max em valores absolutos (l/min) aumenta, enquanto que, em valores relativos (ml.kg -1 .min -1 ), se mantém constante dos 10 aos 15 anos de idade em meninos não treinados. Embora exista essa manutenção dos valores relativos, as intensidades associadas ao VO 2max determinadas por dois diferentes critérios aumentaram nessa faixa etária, sugerindo melhora da EC com o aumento da idade.…”
Section: Discussionunclassified